Tranformasi Digital dalam Pengelolaan dan Penjualan Jamur Merang secara Cerdas dengan Dukungan IoT untuk Optimalisasi Bisnis - Chepy Perdana; Usep Abdul Rosid; Puri Eka Dewi Fortuna; Indah Tri Meidasari; Trianti Dwi Mulyani (JURNAL PENGABDIAN MASYARAKAT INDONESIA, 2026)
This community service activity was carried out with the aim of creating a smart and integrated system in the management and sale of merang mushrooms through digital transformation supported by Internet of Things (IoT) technology to improve business operational efficiency. The alternatives provided solve common problems experienced by mushroom farmers, such as limited market access, inefficient management, and lack of direct monitoring of environmental conditions. The approach applied in this study is Rapid Application Development (RAD) which includes needs collection, system design, implementation, and testing. The output of the web-based system includes modules on farm monitoring, product management, financial record-keeping, and online sales. IoT devices are used to monitor temperature and humidity to keep mold growth conditions ideal. Test results show improved operational efficiency, higher data accuracy, and better accessibility for admins and users. The usefulness of this research lies in the combination of IoT technology with a digital business platform specifically designed for mushroom cultivation, thereby providing smart agriculture solutions that support the sustainable growth and competitiveness of agribusiness